(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The interaction of iodide anion complex of cadmium with basic dye methyl green (MG) has been investigated. Forming ionic associate could be extracted by butylacetate. Maximal light absorption is observed at λ=635–640 nm wavelengths. The optimal acidity of aqueous phase is pH=1, optimal concentration of MG is 6.88⋅10–4–1.204⋅10–3 M and KI – 3⋅10–2–7⋅10–2 M. The range of determined concentration is 0.24–10.0 mcg/mL ( ε636 = 94000 ± 600 L⋅mol–1⋅cm –1). The method was used for determination of cadmium contents in tobacco, meat, milk, sour cream and curd. The method is more sensitive and simple than those reported earlier.